The Effect of Body Mass, Clothing and Death Scene on Postmortem Changes, Rates of Arthropod Colonization and Decomposition on Swiss Mice Cadavers - Tisa, Kery Wesley; Chimbevo, Lenny Mwagandi; Atego, Norbert Adum; Munyekenye, Godwil Ostyula; Mwamburi, Fredrick Mjomba; Gicharu, Gibson Kamau (British Journal of Healthcare and Medical Research, 2024)
Carcass mass affects pattern and rate of carrion decomposition and entomofauna succession. Experimentally, its simultaneous effects on clothing and death scene have not been tested. Simultaneous effects of carcass mass, clothing and death scene were analyzed in this study. A factorial block experiment using four levels Swiss mice carcasses (18g-35g) (N=24); clothing (clothed and unclothed) and death scene (Outdoor and indoor) were made in the summer season. Insects were sampled manually and with pitfall traps, counted, characterized and identified with environmental conditions (ambient and ground temperatures, humidity), carcasses parameters (decomposition mass, postmortem changes and body subsurface and internal temperatures) measured twice a day (10 am and 4 pm). The experimental blocks data were compared to establish the level of significance differences. The results demonstrate that environmental conditions; clothing and death scene affect postmortem changes, carcass mass and decomposition rate. The entomofauna assemblages were more complex, abundant and long lasting affected by carcass mass and death scene with significant difference in blow flies (p>0.005; p=0.0246) and houseflies (P>0.005; P=0.039), whereas clothing is of minor importance. All guilds of carrion insects colonized large to medium large carcasses while small to medium carcasses revealed high underrepresentation of late-colonizing insects such as Nitidulidae Piophilidae and Cleridae. The study findings indicate that standard carcass masses in forensic decomposition studies of about 23g give an incomplete picture of carrion entomofauna. Forensically relevant insects were prolonged during early stages of decomposition with larger carcass masses, indicating cadaver mass as a factor of great importance while their reappearance interval was unrelated to carcass mass or clothing. In conclusion, the study demonstrates that carcass mass is a factor of crucial importance for carrion entomofauna, whereas the effect of clothing is minimal. The study recommends investigation of these factors considering all manner of death using a model mimicking human beings.